The Correlation between Body Mass Index and Albumin Level with Sputum Conversion in AFB-Positive Pulmonary TB Patients in Primary Health Center in Medan, Indonesia - Juli Yosa Mega; Dina Keumala Sari; Juliandi Harahap (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2019)
Tuberculosis (TB) remains a major public issue in Indonesia including in North Sumatra province. Despite reported good efficacy of TB treatment in the region, the success of treatment depends on many factors including nutritional status. This study aims to determine the relationship between Body Mass Index and Albumin level with sputum conversion in AFB-positive pulmonary TB patients.The study was done in two primary health centres in Medan between October and November 2018. A total of 39 newly diagnosed TB patients with confirmed AFB-positve were included in the study.Participants received TB treatment according to the national guidelines. The proportion of participants with below normal, normal and above normal BMI status were 13 (33.3%), 21 (53.9%) and 5 (12.8%), respectively. Level of albumin was determined as normal in 25 participants (64.1%), and the remaining as low. Normal BMI status was significantly associated with increased albumin level (P<0.05). At 2 months follow-up, the sputum conversion was observed in 24 individuals (61.5%), and the conversion was significantly associated with normal BMI and/or normal albumin level (P<0.05). We concluded that nutritional status is an important factor in the success of TB treatment.